Identification, Expression, and Regulation of an Omega Class Glutathione S-transferase in Rhopalosiphum padi (L.) (Hemiptera: Aphididae) Under Insecticide Stress - Balakrishnan, Balachandar; Su, Sha; Wang, Kang; Tian, Ruizheng; Chen, Maohua (Frontiers in Physiology, 2018)
Glutathione S-transferases (GSTs) play an essential role in the detoxification of xenobiotic toxins in insects, including insecticides. However, few data are available for the bird cherry-oat aphid, Rhopalosiphum padi (L.). In this study, we cloned and sequenced the full-length cDNA of an omega GST gene (RpGSTO1) from R. padi, which contains 720 bp in length and encodes 239 amino acids. A phylogenetic analysis revealed that RpGSTO1 belongs to the omega class of insect GSTs. RpGSTO1 gene was highly expressed in transformed Escherichia coli and the protein was purified by affinity chromatography. The recombinant RpGSTO1 displayed reduced glutathione (GSH)-dependent conjugating activity towards the substrate 1-chloro-2, 4-dinitrobenzene (CDNB) substrate. The recombinant RpGSTO1 protein exhibited optimal activity at pH 7.0 and 30°C. In addition, a disc diffusion assay showed that E. coli overexpressing RpGSTO1 increased resistance to cumene hydroperoxide-induced oxidative stress. Real-time quantitative PCR analysis showed that the relative expression level of RpGSTO1 was different in response to different insecticides, suggesting that the enzyme could contribute to insecticide metabolism in R. padi. These findings indicate that RpGSTO1 may play a crucial role in counteracting oxidative stress and detoxifying the insecticides. The results of our study contribute to a better understanding the mechanisms of insecticide detoxification and resistance in R. padi.